2022
DOI: 10.3390/molecules27144643
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and Quantitative Analysis of Ejiao-Related Animal Gelatins through Peptide Markers Using LC-QTOF-MS/MS and Scheduled Multiple Reaction Monitoring (MRM) by LC-QQQ-MS/MS

Abstract: Donkey-hide gelatin, also called Ejiao (colla corii asini), is commonly used as a food health supplement and valuable Chinese medicine. Its growing popular demand and short supply make it a target for fraud, and many other animal gelatins can be found as adulterants. Authentication remains a quality concern. Peptide markers were developed by searching the protein database. However, donkeys and horses share the same database, and there is no specific marker for donkeys. Here, solutions are sought following a da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…E’Jiao, also known as Colla corii asini, is a traditional Chinese medicine derived from donkey-hide gelatine [ 20 , 21 , 22 ]. Modern pharmacology studies demonstrated that E’Jiao could significantly increase haematopoietic stem cells, burst-forming unit-erythroid and colony-forming unit granulocyte-macrophages in the bone marrow.…”
Section: Introductionmentioning
confidence: 99%
“…E’Jiao, also known as Colla corii asini, is a traditional Chinese medicine derived from donkey-hide gelatine [ 20 , 21 , 22 ]. Modern pharmacology studies demonstrated that E’Jiao could significantly increase haematopoietic stem cells, burst-forming unit-erythroid and colony-forming unit granulocyte-macrophages in the bone marrow.…”
Section: Introductionmentioning
confidence: 99%
“…The dietary laws and requirements followed by Muslims (Halal food) and Jews (Kosher food) need to ensure that food products are free from porcine products and by-products, while Hindu customers demand food products of no bovine origin [ 3 , 11 , 12 ]. On the other hand, gelatin is also utilized as a supplement or traditional medicine, such as donkey-hide gelatin, a traditional Chinese medicine manufactured from donkey skin [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%